Interim Review of The Adequacy of The Fund's Precautionary Balances. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
Precautionary balances are a key element of the Fund's multilayered framework to mitigate financial risks. Overall financial risks remain elevated but have not increased significantly since the last review. Staff proposes to leave the medium-term target of SDR 25 billion, and the minimum floor of SDR 15 billion, unchanged at this time. With the projected increase in lending income, the pace of reserve accumulation is expected to remain adequate relative to the medium-term indicative target. The paper also reviews policy factors discussed in recent Board meetings that affect the level and accumulation of reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy